A study of the physical characteristics of the fruits of some types of walnuts "Juglans regia" spread in different locations in Lattakia - الفروي, زينب; محمد نداف; جرجس مخول (Latakia University Journal -Biological Sciences Series, 2024)
This research was conducted at three sites (Ruwaisat Al-Hijal, Mashqita, and Ain Al-Bayda) in Latakia. Samples of walnut fruits and their shells were collected in September 2021 and 2022 from several trees chosen randomly from the sites. Numerous varieties of walnut trees can be found in Latakia, but studies have rarely been presented regarding the characteristics of its fruits and the effect of environmental conditions on them. In this study, the effect of altitude, temperature, rainfall, and soil type on the physical characteristics of walnut fruits was evaluated. Physical nut quality characteristics differed between sampling sites at different altitudes, Ain Al-Bayda region showed significant differences in terms of the average weight of the fruit, the kernel, and the edible portion (14.92g, 11.72g, and 4.97g), respectively, due to the geographical location and soil type. Samples taken from trees grown in red (clay) soil were of higher quality than samples taken from trees grown in white (sandy) soil.